Content Analysis of the Objectives of the Rhetoric Curriculum in Islamic Universities in Aceh in Light of the Integrative Approach to Teaching Arabic Language: تحليل مضمون أهداف منهج البلاغة في الجامعات الإسلامية بأتشيه في ضوء المدخل التكاملي لتعليم اللغة العربية - Muakhir Zakaria; Abdelrahiem, Salah Ibrahiem (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2025)
In this work, The Curriculum Development of The Balaghah lesson in several Islamic Universities in Aceh Province, Indonesia, has been studied to review and present the basics and the proposed vision of the integrative approach in teaching The Arabic Language. This work used the qualitative approach and descriptive analytical approaches utilizing the questionnaire and interview for participants. The population in this work was all students from class IV, to VI with a total of 470 students in the academic year of 2020/2021. The participants of the work were 207 students. Based on the results, the availability of basics of the integrative approach in teaching the Arabic language was at the simple level of the content and teaching methods, and the lack of it was in the purposes, facilities, activities, and evaluation as well as the absence of the statistically significant differences at the level of significance (α = 0.05) between student’s responses to the reality of Balaghah's curriculum that were attributed to Islamic Universities, leading to apply to all universities equally. Therefore, this work recommends working on the reformulation of the Balaghah’s curriculum and developing all elements based on the basics of the integrative approach in teaching of the Arabic language. Besides, the requirement for compatibility and harmonization between the elements of the Balaghah’s curriculum as units that complement each other, and developing training programs to provide the teachers in understanding more the integrative approach, its basics and fields, and the importance of observing it in the elements of the Balaghah’s curriculum.